Intestinal organoids to model cystic fibrosis. Issue 1 (4th July 2019) - van Mourik, Peter; Beekman, Jeffrey M.; van der Ent, Cornelis K.
Recent advances in adult stem cell biology have resulted in the development of organoid culture technologies using a variety of tissue sources such as intestine, lung and kidney [1]. Organoids are three-dimensional, multicellular structures that recapitulate tissue features of the parental organ and are usually grown from donor tissue fragments [1]. As organoids are functional expressions of individual genomes, these cultures are particularly useful to understand how genetic factors contribute to individual disease. As such, they are used to study hereditary diseases such as cystic fibrosis (CF), and more common diseases such as cancer where genetics can influence disease severity and drug efficacy [2, 3]. CF can be studied using patient-specific intestinal organoids. CFTR protein function in intestinal organoids correlates with clinical disease severity and drug testing in organoids could aid in finding drugs for people with rare CFTR mutations. https://bit.ly/2GryRl0